Analisis Sistem Informasi Akuntansi Penjualan Kredit Motor Pada PT. Harpindo Jaya Gubug Kabupaten Grobogan “Studi Kasus Pada PT. Harpindo Jaya Gubug” - Riza Indriyani; Agus Hariyanto (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2022)
This study aims to analyze how the credit sales accounting information system at PT Harpindo Jaya Gubug. This type of research is a qualitative descriptive research. Data were obtained using interview, observation and documentation techniques. The data analysis technique used in this study was descriptive analysis with a qualitative approach. The results of this study state that there is a dual function in the billing section and the accounting department. The credit sales accounting information system document at PT Harpindo Jaya Gubug Grobogan Regency is in accordance with the theory. The company has utilized information technology so that credit sales processing is computerized. Accounting records at PT Harpindo Jaya Gubug need to be repaired by making warehouse cards, inventory cards, accounts receivable cards. While the procedure network that forms the credit sales accounting information system at PT Harpindo Jaya Gubug needs to be improved, namely by having the procedure for recording the cost of goods sold and the procedure for recording receivables.